Lessons from a clinicopathological study of breast cancer - Gangadaran, S. G. D. (International Journal of Research in Medical Sciences, 2016)
Background: It is estimated for every two new breast cancer cases diagnosed, one breast cancer death is reported in India. It is important regional variations in disease behaviour and health care delivery are studied to understand the elevated mortality of breast cancer in India. Methods: In this retrospective study, 198 patient records were scrutinized for breast cancer related demographic data, disease related information, treatment and pathological data. Results: The median age at presentation was 52 years. The results replicated national trends with regards to menopausal status, menarche, parity and breast feeding. Low parity and age at presentation had a strong inverse correlation (P<0.001). EBC (61%) was the commonest with LABC (28%) and Metastatic disease (13.6%) also prevalent. HR positive (47%) molecular type was the commonest with HER 2 neu (30%) and TNBC (22%) types also noted. Core biopsy was the preferred diagnostic test. Metastatic work up had a yield of 13.6%. Mastectomy was the only surgery procedure; none had BCS or sentinel node biopsy. Surgery done by surgical oncologist had better oncological outcomes. Conclusions: Epidemiological profile of breast cancer in south India confirms to national trends. BCS and sentinel node biopsy are considered standard of care in breast cancer care however seems unavailable in government funded hospitals in south India.